Development and characterisation of a liquid phase assisted healable aluminium-magnesium alloy processed by Laser Powder Bed Fusion - Julie Gheysen; Grzegorz Pyka; Bartłomiej Winiarski; Julie Villanova; Florent Hannard; Sophie De Raedemacker; Jack Donoghue; Albert Smith; Aude Simar (Materials & Design)
Strategies to prevent the failure of Al alloys usually aim to optimise composition and microstructure to minimise damage initiation and propagation. However, these are inherently limited in that any damage that nucleates will not disappear. A new liquid phase assisted healable Al-Mg alloy is designed. Its microstructure is composed of a network of a lower melting point eutectic phase distributed within a higher melting point matrix. After damage, a healing heat treatment is applied at a temperature higher than the solidus temperature leading to liquid flow towards the damage sites and their welding. The matrix remains solid maintaining the structural integrity of the component. Correlative tomography combining insights from different 3D electron and X-ray nano-imaging techniques on the same volume of interest before and after healing, highlighted the complete healing and welding of voids and cracks up to 2 µm within the Al-Mg alloy. While softening mechanisms are typically associated with heat treatments of Al alloys, this Al-Mg alloy also maintains strength and ductility after healing heat treatment. This promising concept to increase parts lifetime has potential to be extendable to other non-eutectic 3D printed alloys.